Mensuração da dor durante a anestesia dental e do tempo de latência e duração anestésica pulpar do método de injeção sem agulha : ensaio clínico randomizado - Oliveira, Allan Carlos Araújo de (2018)
Introduction: Pain due to administration of local anesthetics is the primary reason for fear and anxiety in patients seeking treatment, and there are methods and devices to minimize pain caused by the injection. This study aimed to measure the degree of pain during administration of anesthesia, and to determine latency and pulpal anesthesia duration for two anesthetic methods used on the maxilla. Materials and Methods: We conducted a controlled, blind, split-mouth, and randomized study with 41 volunteers who required class I restorations in the maxillary first molars. Local anesthesia was administered with a needleless jet injection (needle free) system and with a carpule syringe (traditional anesthesia; control) using a 30 gauge short needle. The technique used and laterality of the maxilla were previously randomized. The pulp electric tester (PET) measured anesthetic latency and duration. The first molar was restored after measuring latency. The visual analogue scale (VAS) measured the level of pain experienced during the anesthetic techniques. All data were tabulated and sent to a statistician for analysis, and significance level was set as 5%. Results: There was no statistically significant difference in the basal electrical stimulation threshold (mA) and degree of pain measured by VAS between the methods (p>0.05). Anesthetic latency was determined to be 2 minutes for all subjects. Using the Mann-Whitney test, there was a statistically significant difference in the duration of pulpal anesthesia (minutes) between the two techniques (p<0.001). Conclusions: The anesthetic latency time was the same for all subjects that underwent the two anesthetic techniques. The traditional anesthetic method with a carpule syringe showed longer anesthetic duration. Lastly, the difference in pain measured by VAS for the two methods was insignificant.